GUARANTEEING THE RIGHT TO VOTE FOR INDIVIDUALS WHO MARRY UNDERAGE IN THE PERSPECTIVE OF THE CONSTITUTION : Lex Principle Approach Specialist Derogat Legi Genrali and Homo Sacer Theory Giorgio Agamben - Putrawan, Agus Dedi; Andrean, Muhammad; Tabibuddin, Ahmad Saleh; Fauzi, Fauzi (UIN Mataram, 2025)
This study aims to analyze the guarantee of the right to vote for individuals who marry underage from a constitutional perspective with the principle of lex specialis derogat legi generali approach. Normative conflicts occur between the Election Law, the Child Protection Law, the Marriage Law, and the Civil Registration Law. Based on this principle, special laws (lex specialis) can override general laws (lex generalis). Thus, married minors should be able to exercise their right to vote because the Election Law is special in the implementation of elections. This study uses the homo sacer theory of Giorgio Agamben. In this theory, individuals under the age of 17 who marry are considered